Prevention of trismus with different pharmacological therapies after surgical extraction of impacted mandibular third molar - Edin Selimović; Lejla Ibrahimagić-Šeper; Ibrahim Šišić; Suad Sivić; Senad Huseinagić (Medicinski glasnik, 2017)
Aim: To assess prevention and reduction of trismus after surgically extracted impacted mandibular third molars with individual and combined therapy with corticosteroids and anti-inflammatory analgesics. Methods: The research included 60 randomly selected patients (3 groups) attended to the Dental Oral Surgery of the Public Institution Healthcare Center Zenica during the period January-December 2008. Patients of both genders, 18-45 years of age, were presented without pain and other inflammatory symptoms at the time of surgery. According to a scheme established in the research protocol, two medications were administered orally: methylprednisolone (corticosteroid) 32 mg and meloxicam (non-steroidal anti-inflammatory analgesic, NSAID) 15 mg as a single drug, or a combination of both drugs. The level of trismus is assessed on the basis of differences of preoperative and postoperative values of interincisal spaces when fully opening the mouth on the second and the seventh post-operative day. The differences between groups of patients were evaluated by means of Tukey’s HSD test. Results: On the second and on the seventh post-operative day significantly better results were registered in the group that received only corticosteroids and in the group that received both, corticosteroids and NSAIDs compared to the group that received only NSAIDs. A tendency of trismus reduction was present in all patient groups for the second and seventh day after surgery. Conclusion: Prevention and control of postoperative trismus after surgical extraction of impacted mandibular third molars with combined therapy is effective and superior comparing to individual therapy with meloxicam-or methylprednisolone alone.
Keywords: impacted wisdom teeth; corticosteroids; analgesic drug